Etos Kerja dan Nilai Sosial Budaya Masyarakat Tolaki di Kecamatan Tongauna Kabupaten Konawe - Sarmadan . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2013)
ABSTRACT The objective of this research is to investigate, analyze the work ethic of Tolaki tribal communities in rural areas in Konawe, and to identify and analyze the relationship between work ethic and cultural values held by the tribal people in the countryside of Tolaki in Konawe district. The method used in this study is interviewing techniques (in-depth interviews), and observation. Interview technique is conducted in-depth interviews (in-depth interview) either structured or open dialogue (long open-ended interview) to the informant or subject of study in accordance with the objectives of the study. In-depth interviews were asked about work ethics and cultural values in the Tolaki community. While observational techniques use to support data analysis and this technique is one pretty good way to collect data in the field of qualitative research. Observation technique is basically done at the beginning of the assessment or collection of information about the location of the research, to make observations during the execution of a job and or customs and activities of cal communities (at the sites). Key words: work ethic, social value, cultural value